Geochemial patterns and firing technology research on ceramic glazed tiles from the 17th-20th centuries (Lisbon region, Portugal) - Dias, Isabel M. (2021)
A set of 17th – 20th century glazed tiles supplied by the Department of Cultural Heritage tile collection, Lisbon City Hall, is studied in this work. The tiles were described and classified in a chronological point of view and analytical work includes chemical and mineralogical characterization of the ceramic bodies and mortars by instrumental neutron activation analysis and X-ray diffraction. Most tile bodies consist mainly of quartz, gehlenite and calcite in variable proportions; commonly these main phases are accompanied by high temperatures phases, namely wollastonite or diopside, pointing to a Ca- or Mg-rich raw material, and mullite (in one sample) indicating the use of non-carbonated raw materials. Small amounts of K-feldspar and hematite are present in most tiles, whereas analcime, plagioclase, vaterite and cristobalite are found in just a few samples. Chemical composition points to a certain homogeneity within 18th century tile bodies; the 20th century samples analysed are heterogeneous and have a different rare earth elements (REE) pattern, two are enriched in the first transition row elements, pointing to higher amounts of ferromagnesian minerals, and the other has lower amounts of Na, Fe, Cr and Co, and higher of Cs, light rare earth elements (LREE), Th and U suggesting high aluminium silicates content. The 17th century samples have a more heterogeneous chemical composition and higher contents of As and Na, which is explained by the presence of analcime. The ancient tiles have a general depletion of chemical elements, probably due to a dilution effect of the higher calcite content. The mortars are all lime rich, but the 20th century ones have a general enrichment in all elements, and more k-feldspar and mica.